2016
DOI: 10.21070/picecrs.v1i1.501
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Attitudes and Beliefs Towards the Use of Student-Centred Learning in English Language Classes

Abstract: ABSTRACT:This study was conducted to examine teachers' attitudes and beliefs towards the use of StudentCentred Learning in English language classes. In addition, it also sought to examine the extent of studentcentred learning practices amongst primary school teachers have on their students' performance in the English language. A survey was carried out to collect data from 147 primary school English language teachers in Perlis. The questionnaires were used to determine the teachers' beliefsand attitudes towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…They understand that a student-centered approach to teaching the wants and needs of the students. Moreover, the findings of this study are in line with the research [16], who demonstrated positive attitudes of the EFL teachers toward student-centered learning. In addition, the results of this study are consistent with previous study [23], whose findings indicated that both students and teachers had positive attitudes toward implementing learner centered pedagogy.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…They understand that a student-centered approach to teaching the wants and needs of the students. Moreover, the findings of this study are in line with the research [16], who demonstrated positive attitudes of the EFL teachers toward student-centered learning. In addition, the results of this study are consistent with previous study [23], whose findings indicated that both students and teachers had positive attitudes toward implementing learner centered pedagogy.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the results of this study are consistent with previous study [23], whose findings indicated that both students and teachers had positive attitudes toward implementing learner centered pedagogy. Likewise, the findings of this study align with the research [16], who noted that there were positive attitudes of English language teachers towards studentcentered learning. The results of this study are also consistent with the study [31], who claim that although teachers and students hold positive attitudes toward student-centered approach, they still encounter several issues that prevent the application of the student-centered approach in the classroom.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, despite the changes and continual improvements in the education system, differentiated instruction has not often been put into practice, and no much difference has been seen in the teaching methods applied by teachers as compared to before [6], [7]. It is found that traditional teaching methods which are teacher-centered are still dominating instruction [8], [9]. Besides, teachers tend to implement direct instruction in their teaching and learning process too [10].…”
Section: Introductionmentioning
confidence: 99%